TRADE WAR BETWEEN UNITED STATE OF AMERICA AND CHINA REVIEWED FROM THE RETALIATION PRINCIPLE - Savira, Gina Nafsah; Latifah, Emmy (Tadulako Law Review, 2019)
This paper aims to examine how the principle of retaliation in the case of a trade war between the United States and China is now happening. The General Agreement on Tariff and Trade (GATT) in the World Trade Organization (WTO) has regulated acts of retaliation in the context of international trade. Even though there are different conceptions of retaliation in the two international legal frameworks, they both recognize the retaliation action. The results of the study shows that the economic policies carried out by the United States are called trade remedies in the form of protestionism which aimed to minimize the negative impact of imports on domestic products. Furthermore, actions taken by China are one example of the remedial actions in the form of retaliation. WTO has a remedy mechanism which is divided into three types, namely: (a) the plaintiff withdraws or changes actions that are not in accordance with the WTO; (b) compensation; and (c) delaying concessions or commonly called retaliation.